Assessment and control of a photovoltaic energy storage system based on the robust sliding mode MPPT controller. (1st December 2016) - Yatimi, Hanane; Aroudam, Elhassan
Highlights: Detailed mathematical model of the Standalone PV storage system is presented. The influence of real climatic conditions on I-V and P-V curves is carried out. Simulation results are used to assess the robustness of the proposed MPPT controller. Abstract: The energy produced by the photovoltaic systems is very intermittent and depends enormously on the weather conditions. As the output characteristic of a photovoltaic (PV) module is nonlinear and changes with solar irradiance and the cell's temperature, its maximum power point (MPP) is not constant. Therefore, a maximum power point tracking (MPPT) technique is needed to draw peak power from the PV module to maximize the produced energy under varying conditions. This paper presents an assessment and control of a stand-alone photovoltaic system with battery storage using the robust sliding mode MPPT control for DC/DC boost converter operating in continuous conduction mode; under varying meteorological conditions. Simulation results are presented to verify the simplicity, the stability and the robustness of this control technique against changes in weather conditions.